2022
DOI: 10.3390/coatings12010087
|View full text |Cite
|
Sign up to set email alerts
|

Epitaxial Growth and Optical Properties of Laser Deposited CdS Thin Films

Abstract: In this study, cadmium Sulfide (CdS) thin films were synthesized on quartz substrates using an infrared pulsed laser deposition (IR-PLD) technique under high vacuum (~10−6 Torr) conditions. X-ray diffraction was used to evaluate the structural features. According to X-ray analysis, the deposited CdS films are crystalline and have a favored orientation on a plane (110) of an orthorhombic. The peak intensity and the average crystallite size increases with increasing the film thickness. After annealing at 300 °C,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Te performance of various thicknesses of CdS without a MB sensitizer has been studied, and the short circuit current density J SC increases with increasing the thickness, reaching 0.462 mA/cm 2 with a power conversion efciency of 0.018% for FTO/3 layer CdS/electrolyte/carbon/FTO device, as shown in Figure 7(a). Gadalla et al [37] studied the infuence of increasing the thickness of CdS thin flms on the output photocurrent, and they found that an increment in the photocurrent with increased thickness. Other researchers the results by increasing the thickness which agrees with [38][39][40].…”
Section: Optical Propertiesmentioning
confidence: 99%
“…Te performance of various thicknesses of CdS without a MB sensitizer has been studied, and the short circuit current density J SC increases with increasing the thickness, reaching 0.462 mA/cm 2 with a power conversion efciency of 0.018% for FTO/3 layer CdS/electrolyte/carbon/FTO device, as shown in Figure 7(a). Gadalla et al [37] studied the infuence of increasing the thickness of CdS thin flms on the output photocurrent, and they found that an increment in the photocurrent with increased thickness. Other researchers the results by increasing the thickness which agrees with [38][39][40].…”
Section: Optical Propertiesmentioning
confidence: 99%
“…[6] CdS films are used as window materials in heterojunction solar cells because of their wide bandgap, high transmittance, and low-cost techniques. Research indicated that CdS thin films have been produced by different deposition techniques, such as; evaporation, [7] RF sputtering, [8] spray pyrolysis, [9] chemical bath, [10] pulsed laser deposition [11] and electrodeposition. [12] Within these deposition techniques, electrodeposition is considered one of the low-cost methods for semiconductor thin film fabrication.…”
Section: Introductionmentioning
confidence: 99%